35 Clinical management of gynecologic cancer patients during COVID-19 pandemia: the experience of day hospital tumori femminili of fondazione policlinico agostino gemelli, IRCCS. (13th November 2020) - Palluzzi, E; Corrado, G; Bolomini, G; Vertechy, L; Bottoni, C; Teodorico, E; Marchetti, C; Distefano, M; Scambia, G; Ferrandina, G
Abstract : Introduction: During COVID-19 pandemia there was the need to reorganize cancer care. Italian and European association published recommendations to evaluate the risk/benefit ratio of delaying anticancer adjuvant/neoadjuvant/first line treatment, delaying all other treatments or manteinance therapy, reducing the risk for medical and paramedical staff. In this scenario, the aim of our work is to retrospective evaluate the activity of Day Hospital (DH) Tumori Femminili of Fondazione Policlinico Agostino Gemelli, IRCCS, for the medical management of gynecologic cancer patients between February and April 2020. Methods: Based on published recommendations, with local Health Direction guidelines we draft the Security Protocol to modulate the access of patients into the DH: to perform visits only of new patients or for clinical urgency and to convert on telemedicine the other contacts; to perform a phone/telematic pre-triage the day before the scheduled access and an 'in site' pre-triage with measurement of body temperature and administration of a survey for the self-certification of absence risk factors for COVID-19 infection; no caregivers were allowed into DH; surgical masks and gloves were obligatory for anyone. Results: We registered 3223 accesses/contacts into our DH for intravenous/oral chemotherapy and visits. The activity was similar to that recorded in 2019 in the same two-month period (3311 accesses). Despite the high patients flow we had only two cases of confirmed COVID-19 infection and no cases among healthcare staff. Conclusions: Based on the adopted Security Protocol we have guaranteed continuity of care to all our patients and limited the spread of the COVID-19 infection.